Kandungan Klorofil dan Kerapatan Stomata Spesies Invasif Chromolaena odorata pada Kondisi Naungan yang Berbeda - Devi Eka Lestari; Nida Lidya Susanti; Rohimatul Anwar (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2026)
Kirinyuh plant (Chromolaena odorata) is one of the most aggressive invasive plant species, with a strong ability to colonize diverse habitats under varying environmental conditions. Light availability is a key environmental factor influencing the establishment and spread of invasive species, as it affects leaf physiological and anatomical traits related to photosynthesis and resource use. This study aimed to evaluate the ecophysiological responses of C. odorata under different shading conditions based on chlorophyll content and stomatal characteristics. Leaf samples were collected from plants growing in open and shaded habitats. The parameters observed included chlorophyll a, chlorophyll b, total chlorophyll content, and stomatal density. Chlorophyll was analyzed using a 95% ethanol extraction method followed by UV–Vis spectrophotometry. Stomatal density was determined through leaf sectioning and safranin staining. The results showed that shaded plants had higher chlorophyll a, chlorophyll b, and total chlorophyll contents compared to those in open habitats, while stomatal density was lower under shaded conditions. These findings indicate that C. odorata can adjust its physiological and anatomical traits in response to light variation, supporting its ecological adaptability.